Compressive Strength Performance of High-Volume Fly Ash Concrete with CaCO3 Addition - Wibowo, Yosi Noviari; Tatas, Tatas; Tajunnisa, Yuyun; Mawardi, Amalia Firdaus; Zanah, Miftaqul (IPTEK The Journal of Engineering, 2025)
This study investigates the compressive strength performance of High-Volume Fly Ash (HVFA) concrete with added CaCO₃ as a sustainable alternative to Ordinary Portland Cement (OPC) for infrastructure applications. The experimental research replaces a significant portion of cement with fly ash—a byproduct of coal combustion—aiming to reduce greenhouse gas emissions associated with concrete production. Two HVFA concrete mixtures were developed, substituting 37% and 47% of cement content with fly ash and adding 3% CaCO₃ to enhance mechanical properties. Material characterization, including XRF and XRD analysis, confirmed the suitability of fly ash for concrete production based on ASTM C618-19 standards. Aggregate gradation, moisture content, and specific gravity tests were conducted to optimize the mix design. Compressive strength tests were performed at 7, 14, and 28 days, showing that HVFA concrete with 37% fly ash substitution achieved higher strength values, reaching 25.92 MPa at 28 days, compared to the 47% mix, which reached 24.68 MPa. Slump tests indicated sufficient workability, with a measured slump of 10 cm for FA37C3 and 12 for FA47C3. These findings suggest that HVFA concrete with moderate fly ash substitution, complemented by CaCO₃ addition, can achieve compressive strength and workability comparable to OPC, supporting the development of environmentally friendly concrete solutions.